2013
DOI: 10.1111/jasp.12019
|View full text |Cite
|
Sign up to set email alerts
|

Out‐group trust, intergroup anxiety, and out‐group attitude as mediators of the effect of imagined intergroup contact on intergroup behavioral tendencies

Abstract: We investigated whether imagining contact with an out‐group member would change behavioral tendencies toward the out‐group. In Experiment 1, British high school students who imagined talking to an asylum seeker reported a stronger tendency to approach asylum seekers than did participants in a control condition. Path analysis revealed this relationship was mediated by out‐group trust and, marginally, by out‐group attitude. In Experiment 2, straight undergraduates who imagined an interaction with a gay individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 40 publications
5
150
0
3
Order By: Relevance
“…One of the prominent reasons why ethnic minority groups experience intergroup anxiety and show negative outgroup attitudes is that they have negative expectations from the part of the majority group members (e.g., Saguy et al, 2009). Previous research has shown that awareness and concern of being the target of prejudice leads to the negative evaluation of outgroup members (e.g., Shelton, 2003;Pinel, 1999 Turner et al 2013) have only concentrated on contact that is initiated by the outgroup member, which can indicate that the other group member is willing to engage in contact. Therefore, by investigating the perception of the outgroup's attitudes, we extended previous research, drawing attention to how the contact partner is evaluated during the scenario.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the prominent reasons why ethnic minority groups experience intergroup anxiety and show negative outgroup attitudes is that they have negative expectations from the part of the majority group members (e.g., Saguy et al, 2009). Previous research has shown that awareness and concern of being the target of prejudice leads to the negative evaluation of outgroup members (e.g., Shelton, 2003;Pinel, 1999 Turner et al 2013) have only concentrated on contact that is initiated by the outgroup member, which can indicate that the other group member is willing to engage in contact. Therefore, by investigating the perception of the outgroup's attitudes, we extended previous research, drawing attention to how the contact partner is evaluated during the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, if direct positive intergroup contact is difficult to occur naturally, such a positive contact may be mentally simulated. Therefore, the basic idea behind imagined contact research has been providing diverse positive intergroup outcomes such as improved explicit and implicit attitudes (Turner & Crisp, 2010;Vezzali, Capozza, Giovannini, & Stathi, 2012), positive behavioral intentions towards the outgroup (Husnu & Crisp, 2010a), projection of positive traits to the outgroup (Stathi & Crisp, 2008), outgroup trust (Turner, West, & Christie, 2013), and reduced prejudice and intergroup anxiety (Kuchenbrandt, Eyssel, & Seidel, 2013) by simply asking participants to imagine positive contact with an outgroup member.…”
Section: Recent Advances In Imagined Contact Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of research has demonstrated that positive contact between members of different social groups fosters intergroup liking, intergroup trust, and willingness to form meaningful cross-group friendships (Christ et al, 2010;Page-Gould, MendozaDenton, & Tropp, 2008;Tam, Hewstone, Kenworthy, & Cairns, 2009;Turner, West, & Christie, 2013;Wagner, Tropp, Finchilescu, & Tredoux, 2008). In addition, positive contact reduces social distance and prejudice 1 toward members of the opposing group (Barlow, Louis & Hewstone, 2009;Barlow, Louis, & Terry, 2010;Paolini, Hewstone, Cairns, 2007;Paolini, Hewstone, Cairns, & Voci, 2004;.…”
Section: General Introductionmentioning
confidence: 99%